In vitro anti-Candida activity and single crystal X-ray structure of ({(1E)-[3-(1H-imidazol-1-yl)-1-phenylpropylidene]amino}oxy)(4-nitrophenyl)methanone - Attia, Mohamed I.; Ghabbour, Hazem A.; Zakaria, Azza S.; Fun, Hoong-Kun (Bangladesh Journal of Pharmacology, 2014)
Synthesis, characterization, and anti-Candida activity of ({(E)-[3-(1H-imidazol-1-yl)-1-phenylpropylidene]amino}oxy)(4-nitrophenyl)methanone (4) are reported. Compound 4 showed anti-Candida albicans activity (MIC = 0.6862 µmol/mL) being nearly 5-fold more potent than the gold standard antifungal drug, fluconazole (MIC ˃ 3.265 µmol/mL), on the clinical isolates of Candida albicans. Single crystal X-ray structure of the title compound 4 confirmed its assigned (E)-configuration. The compound crystallizes in the triclinic, P-1 (no. 2), a = 6.4633 (1) Å, b = 11.1063 (2) Å, c = 12.9872 (2) Å, α = 67.650 (1)°, β = 86.415 (1)°, γ = 86.776 (1)°, V = 860.01 (3)Å3, Z = 2, R(F) = 0.046, wR(F2) = 0.139, T = 296 K. The crystal structure is stabilized by weak intermolecular C—H•••O hydrogen interactions.